8.4k views
3 votes
X= root (y-1/y+1) ( make “y” as subject. ) number 19

X= root (y-1/y+1) ( make “y” as subject. ) number 19-example-1
User Jconlin
by
6.6k points

1 Answer

6 votes

Answer:

y = (x² + 1) / (1 – x²)

Explanation:

x = √[(y – 1)/(y + 1)]

We can make y the subject of the expression as shown below:

x = √[(y – 1)/(y + 1)]

Take the square of both side

x² = (y – 1) /(y + 1)

Cross multiply

x²(y + 1) = (y – 1)

Clear bracket

x²y + x² = y – 1

Rearrange

x² + 1 = y – x²y

Factorise

x² + 1 = y(1 – x²)

Divide both side by (1 – x²)

y = (x² + 1) / (1 – x²)

User Enrico Stahn
by
6.0k points